Evidence on tuberculosis in migrants at Brazil's international borders: A scoping review - Débora de Almeida Soares; Aline Placeres; Ricardo A. Arcêncio; Inês Fronteira (Elsevier, 2023)
Objective: to map scientific evidence on the extent of tuberculosis in migrants from the international borders between Brazil and the countries of South America. Design: Scoping review of quantitative, qualitative and mixed studies. The research was conducted between February and April 2021. The terms "migrants", "tuberculosis", "Brazil", "Uruguay", "Paraguay", "Bolivia", "Peru", "British Guiana" "English Guiana", "French Guiana", "Suriname", "Venezuela", "Argentina", "Colombia" combined with Boolean operators "AND" and "OR" to identified relevant documents. Studies addressing tuberculosis on migrants from international borders of Brazil were included. Pubmed Central (PMC), LILACS (Scientific and technical literature of Latin America and the Caribbean/BVS), Scopus (Elsevier), Scielo (Scientific Electronic Library Online) and gray literature CAPES thesis database were searched. The study was carried out in three stages where the data was selected and extracted by two independent reviewers for full reading. Results: A total of 705 articles were extracted from the databases chosen for the search, 04 master's dissertations and 01 doctoral thesis. Of these 456 were excluded because they did not meet at least one of the eligibility criteria for this SR and 4 were further excluded because they were duplicates who had not been previously identified. A total of 58 documents were, thus, selected for assessment of the full text. Of these, 40 were further excluded for not meeting at least one of the eligibility criteria. A total of 18 studies were included for data collection: 15 articles, 2 master's dissertations and 1 doctoral thesis, produced between 2002 and 2021. Conclusion: This scoping review mapped the existing evidence on tuberculosis at the international borders of Brazil and on access of immigrants with tuberculosis to health services in Brazil. Descriptors: tuberculosis; immigrants; public health surveillance; epidemiological surveillance; sanitary control of borders; health services accessibility.